Surface Sensing for Biofilm Formation in Pseudomonas aeruginosa - Chang, Chien-Yi (Frontiers in Microbiology, 2018)
Aggregating and forming biofilms on biotic or abiotic surfaces are ubiquitous bacterial behaviors under various conditions. In clinical settings, persistent presence of biofilms increases the risks of healthcare-associated infections and imposes huge healthcare and economic burdens. Bacteria within biofilms are protected from external damage and attacks from the host immune system and can exchange genomic information including antibiotic-resistance genes. Dispersed bacterial cells from attached biofilms on medical devices or host tissues may also serve as the origin of further infections. Understanding how bacteria develop biofilms is pertinent to tackle biofilm-associated infections and transmission. Biofilms have been suggested as a continuum of growth modes for adapting to different environments, initiating from bacterial cells sensing their attachment to a surface and then switching cellular physiological status for mature biofilm development. It is crucial to understand bacterial gene regulatory networks and decision-making processes for biofilm formation upon initial surface attachment. Pseudomonas aeruginosa is one of the model microorganisms for studying bacterial population behaviors. Several hypotheses and studies have suggested that extracellular macromolecules and appendages play important roles in bacterial responses to the surface attachment. Here, I review recent studies on potential molecular mechanisms and signal transduction pathways for P. aeruginosa surface sensing.